Dynamic dissociation of trions in conjugated polymers. (1st March 2017) - Wang, Y. D.; Zhang, Y. L.; Meng, Y.; Zhang, X. G.; Di, B.; An, Z.
Abstract: Within a one-dimensional tight-binding model, the dynamic dissociation processes of trions under an external electric field have been investigated using a nonadiabatic evolution method. We demonstrate that the dissociation of the trion under an applied electric field is more difficult than in the case for either the polaron or the bipolaron. Considering the effect of the electron-electron interactions, it is found that the on-site Coulomb interactions reduce while the nearest-neighbor interactions enhance the stability of the trion. Furthermore, due to the competition between the on-site Coulomb and the nearest-neighbor interactions, the static trion presents two typical configurations in general, i.e., a bound state of an exciton and a polaron or a bound state of a bipolaron and an opposite charged polaron. Accordingly, the outcome of the trion dissociation is closely related to its static configuration.